PENYELENGGARAAN PERIZINAN DAN NON PERIZINAN DI KABUPATEN BEKASI - Waluyo Zulfikar (Universitas Jenderal Ahmad Yani, 2019)
The problem of this research is explore licensing dan non-licecensing policy services in Bekasi Regency. That must be carried out properly to the community. but in practice, the implementation of licensing in Bekasi Regency is still not going well, this condition actually keeps the concept of licensing away from the ideal concept, standard rules regarding the institution and authority of the Investment Agency and One Stop Integrated Service which are not yet clear have triggered various problems in the permit processing process. existing businesses in Bekasi Regency. The researcher conducted an in-depth analysis using a qualitative descriptive analysis method where the results of this study concluded that efforts to improve and improve licensing and non-licensing services in Bekasi Regency were divided based on several series of priority choices. Determination of priority options based on parameters of depth of resolution efforts, length of time for problem handling and readiness of human resources executing policies, programs and government activities in Bekasi Regency. Errors in the interpretation of national regulations related to licensing and non-licensing policies will result in the unclear function of permits. The same function is regulated in different regulations so that it is over regulated. It is necessary to improve the licensing and non-licensing policies, where based on the results of this study there are still many permits that were born because of the discretion of the regional government, or were born in the daily practice of governing. Keywords: Licensing, Non-Licensing, Bekasi Regency